The consequences of counterterrorism - Crenshaw, Martha (Russell Sage Foundation, 2010)
Counterterrorism regimes and the rule of law : the effects of emergency legislation on separation of powers, civil liberties, and other fundamental constitutional norms / John E. Finn -- The uses and abuses of terrorist designation lists / Chantal de Jonge Oudraat and Jean-Luc Marret -- Immigration policy as counterterrorism : the effects of security on migration and border control in the European Union / Gallya Lahav -- The social contract and the three types of terrorism : democratic society in the United Kingdom after 9/11 and 7/7 / Dirk Haubrich -- Confronting terrorism in Northern Ireland and the Basque country : challenges for democracy and legitimacy / Rogelio Alonso -- French responses to terrorism from the Algerian war to the present / Jeremy Shapiro -- Germany's response to 9/11 : the importance of checks and balances / Giovanni Capoccia -- The consequences of counterterrorist policies in Israel / Ami Pedahzur and Arie Perliger -- Terrorism as conventional security for democracies : America, Japan, and military action in the Asia-Pacific / David Leheny